2023
DOI: 10.18632/aging.204714
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of metabolism-related genes signature and immune infiltration landscape of rheumatoid arthritis based on machine learning

Abstract: Rheumatoid arthritis (RA) causes irreversible joint damage, but the pathogenesis is unknown. Therefore, it is crucial to identify diagnostic biomarkers of RA metabolism-related genes (MRGs). This study obtained transcriptome data from healthy individuals (HC) and RA patients from the GEO database. Weighted gene correlation network analysis (WGCNA), the least absolute shrinkage and selection operator (LASSO), and random forest (RF) algorithms were adopted to identify the diagnostic feature biomarker for RA. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The onset and progression of RA are influenced by various pathophysiological factors including environmental and genetic triggers [ 3 ]. Recent studies have suggested that immunodeficiency is a characteristic feature of RA and plays a critical role in its early stages [ 4 , 5 ]. In contrast to osteoarthritis, RA involves the infiltration of several immune cells, such as macrophages, T cells, neutrophils, and B lymphocytes, into the synovial membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The onset and progression of RA are influenced by various pathophysiological factors including environmental and genetic triggers [ 3 ]. Recent studies have suggested that immunodeficiency is a characteristic feature of RA and plays a critical role in its early stages [ 4 , 5 ]. In contrast to osteoarthritis, RA involves the infiltration of several immune cells, such as macrophages, T cells, neutrophils, and B lymphocytes, into the synovial membrane.…”
Section: Introductionmentioning
confidence: 99%